2016
DOI: 10.1016/j.brat.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

The impact of treatment condition and the lagged effects of PTSD symptom severity and alcohol use on changes in alcohol craving

Abstract: Given the high rates of comorbidity between posttraumatic stress disorder (PTSD) and substance use disorder (SUD), we investigated an integrated treatment for these disorders. Individuals with comorbid PTSD and alcohol dependence were randomized to receive naltrexone or placebo, with or without prolonged exposure (PE). All participants also received BRENDA (supportive counseling). The naltrexone plus PE group showed a greater decline in alcohol craving symptoms than those in the placebo with no PE group. The P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 62 publications
(77 reference statements)
1
15
0
Order By: Relevance
“…In terms of between-group differences, individuals with OUD reported significantly greater reductions in alcohol craving relative to participants in the non-OUD comparison group. This finding is consistent with the findings of Kaczkurkin, Asnaani, Alpert, and Foa (2016), who demonstrated that individuals with more severe PTSD symptomatology showed greater improvements in alcohol craving over time. Together, these findings suggest that individuals with more severe PTSD and SUD symptomatology have more room for improvement over time.…”
Section: Discussionsupporting
confidence: 91%
“…In terms of between-group differences, individuals with OUD reported significantly greater reductions in alcohol craving relative to participants in the non-OUD comparison group. This finding is consistent with the findings of Kaczkurkin, Asnaani, Alpert, and Foa (2016), who demonstrated that individuals with more severe PTSD symptomatology showed greater improvements in alcohol craving over time. Together, these findings suggest that individuals with more severe PTSD and SUD symptomatology have more room for improvement over time.…”
Section: Discussionsupporting
confidence: 91%
“…In an RCT for concurrent PTSD and SUD treatment, Hien et al (2010) found that SUD improvement reliably followed PTSD improvement, but found no converse association between SUD change and subsequent PTSD improvement. Recently, Kaczkurkin, Asnaani, Alpert, and Foa, (2016) extended growth models to examine the lagged effects of PTSD symptoms on alcohol craving within a trial of integrated treatment combinations for PTSD and SUD (naltrexone vs. placebo, with or without prolonged exposure). When PTSD symptoms (at time t ) were compared to subsequent alcohol craving (at time t + 1), improvement in PTSD symptom severity was associated with diminished alcohol craving; however, no interactions between PTSD symptoms and the four treatment combinations were observed.…”
mentioning
confidence: 99%
“…In clinical settings, patients presenting for treatment with PTSD/SUD comorbidity are commonly referred to SUD-only treatment first, and some are later referred to PTSD treatment [ 15 , 16 ]. However, prior research shows that integrated and concurrent treatments for PTSD/SUD can effectively reduce symptoms of PTSD while also significantly decreasing symptoms of SUD [ 12 , 17 , 18 , 19 , 20 ]. It may be that integrated treatments are more effective for complex symptom presentations, such as that observed in PTSD/SUD comorbidity, than treatments designed to treat one disorder exclusively.…”
Section: Introductionmentioning
confidence: 99%
“…It may be that integrated treatments are more effective for complex symptom presentations, such as that observed in PTSD/SUD comorbidity, than treatments designed to treat one disorder exclusively. Importantly, reductions in PTSD symptoms following treatment of PTSD/SUD are associated with corresponding reductions in SUD symptoms [ 12 , 18 , 19 ]. In contrast, reductions in SUD symptoms have not been associated with corresponding reductions in PTSD symptoms [ 12 , 18 ].…”
Section: Introductionmentioning
confidence: 99%